2013
DOI: 10.1155/2013/723645
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a WMR for Trajectory Tracking Control: Experimental Results

Abstract: This paper reports a solution for trajectory tracking control of a differential drive wheeled mobile robot (WMR) based on a hierarchical approach. The general design and construction of the WMR are described. The hierarchical controller proposed has two components: a high-level control and a low-level control. The high-level control law is based on an input-output linearization scheme for the robot kinematic model, which provides the desired angular velocity profiles that the WMR has to track in order to achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 20 publications
0
17
0
3
Order By: Relevance
“…After carrying out the review of the literature associated with design of controllers for the trajectory tracking task in differential drive WMRs, it was found that, generally, this task has been solved in three directions: (a) by only using the kinematic or dynamic model of the mechanical structure , (b) by employing the kinematic/dynamic model of the mechanical structure along with the dynamics of the actuators [85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103], and (c) by considering the kinematic model of the mechanical structure along with the dynamics of the actuators and power stage [104,105]. In the last direction, contributions that have carried out interesting efforts are [106][107][108][109][110][111][112][113][114].…”
Section: Discussion and Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…After carrying out the review of the literature associated with design of controllers for the trajectory tracking task in differential drive WMRs, it was found that, generally, this task has been solved in three directions: (a) by only using the kinematic or dynamic model of the mechanical structure , (b) by employing the kinematic/dynamic model of the mechanical structure along with the dynamics of the actuators [85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103], and (c) by considering the kinematic model of the mechanical structure along with the dynamics of the actuators and power stage [104,105]. In the last direction, contributions that have carried out interesting efforts are [106][107][108][109][110][111][112][113][114].…”
Section: Discussion and Contributionmentioning
confidence: 99%
“…Recently, Zuo et al [87] described a control strategy that integrates a kinematic control and an adaptive wavelet neural network, which is robust to disturbances. Lastly, Silva-Ortigoza et al [88] proposed a robust hierarchical controller where the high-level control is based on inputoutput linearization for the mechanical structure and the lowlevel control is based on a PI control for the actuators.…”
Section: Kinematic Modelmentioning
confidence: 99%
“…Un controlador basado en un control cinemático y en redes neuronales adaptivas fue desarrollado por Zuo et al en [16]. Finalmente, un controlador jerárquico de dos niveles fue diseñado por Silva-Ortigoza et al en [17]; en el nivel alto se propuso un control por linealización entrada-salida para la estructura mecánica del RMR y en el nivel bajo un control PI para los motores de CD.…”
Section: A Modelo Cinemático De La Estructura Mecánicaunclassified
“…Una vez realizada la revisión de la literatura asociada a la problemática de seguimiento de trayectoria en RMRs tipo diferencial, se detectó que, en general, los controles reportados se han diseñado desde las siguientes dos perspectivas: a) cuando se considera únicamente el modelo cinemático [4]- [13] o dinámico [18]- [23] de la estructura mecánica y b) cuando se consideran el modelo cinemático o dinámico de la estructura mecánica y el modelo matemático de los actuadores; [14]- [17] y [24]- [28], respectivamente. Mientras que el modelo matemático asociado con la etapa de potencia, junto con los otros dos subsistemas, no ha sido considerado en el diseño de controles promedio de RMRs.…”
Section: Discusión Del Estado Del Arte Y Contribuciónunclassified
“…The dynamical parameters of the motors are estimated by experiments based on their speci cation. With the same strategies proposed in [21], and assuming the two motors have the same parameters, the approximated dynamic model of the DC motor can be described byω…”
Section: Implementation Of the Control With DC Motorsmentioning
confidence: 99%